Assessment of health, safety and environmental implications for water quality management in the Global South: a case study of Lagos, Federal Republic of Nigeria - Olaniyi, T. K.; Nwankwo, N.; Idahose, U. E. (International Journal of e-Healthcare Information Systems, 2023)
The general health of life is directly influenced by water quality and in order to maintain a healthy community, sufficient attention should be paid to managing water quality. This paper assesses the implications of health, safety and environmental or water quality management in the Global South (GS) using Lagos, Nigeria as a case study. Water security and water pollution are critical problems to human health, economic and environmental activities and much so in GS. Contaminated drinking water from industrial wastes, chemicals, toxic substances and wastewater as a result of industrial and agricultural activities causes serious health challenges to human. Global North (GN) countries have however, significantly improved water quality from past decades and implemented policies affecting water quality management. Despite regulations and policies towards a sustainable water quality in the GS, industrial activities in big cities like Lagos, have contributed hugely to water bodies pollution through indiscriminate waste disposal. Inadequate implementation of policies and regulations still persist as a challenge for water quality management. Comparative study between the GS countries, i.e., Nigeria and the GN countries (i.e., Iceland and Sweden) reveals that the GN adopts a strict compliance and transparency level as a preventive management strategy in ensuring sustainable water quality management - this is significantly lacking in Lagos, Nigeria. Emphatically, regulatory bodies in Lagos and Nigeria as a whole should effectively and regularly monitor water quality for drinking purpose and on-site waste water. Water treatment parameters and analysis should be taken as important aspect for water quality management. The consequent problems of water quality management in Nigeria, has affected her socio-economic tendencies. This paper insists on adopting suitable recommendations that improves the health, safety and environment of people by improving water quality management practices. Future work will include the use of ...